Development and removal ability of non-toxigenic Aspergillus section Flavi in presence of atrazine, chlorpyrifos and endosulfan - Barberis, Carla Lorena (2019)
This study evaluated the in vitro effect of three concentrations of atrazine, chlorpyrifos and endosulfan on the growth parameters of four non-toxigenic Aspergillus section Flavi strains. The capacity of the strains to remove these pesticides in synthetic medium was also determined. The growth parameters were measured on soil extract solid medium supplied with 5, 10 and 20 mg/l of each pesticide, and conditioned to -0.70, -2.78, -7.06 and -10.0 water potential (MPa). Removal assays were performed in Czapek Doc (CZD) medium supplied with 20 mg/l of each pesticide under optimal environmental conditions (0.98 water activity-aW and 25°C). The residual levels of each pesticide were detected by reversed-phase HPLC/fluorescence detection system. The lag phases of the strains significantly decreased in the presence of the pesticides respecting to the control media. This result indicates a fast adaptation to the conditions assayed. Similarly, the mycelial growth rates in the different treatments increased with some pesticide concentrations. A. oryzae AM 1 and AM 2 strains showed high percentages of atrazine degradation (above 90%), followed by endosulfan (56 and 76%) and chlorpyrifos (50 and 73 %) after 30 days of incubation. A significant correlation (p˂0.001, r=0.974) between removal percentages and growth rate was found. This study shows that non-toxigenic Aspergillus section Flavi strains from agricultural soils are able to effectively grow in the presence of high concentrations of atrazine, chlorpyrifos and endosulfan over a wide range of MPa conditions. Moreover, these strains have the capacity to remove in vitro high levels of these pesticides in short time.